A Contingent View of Partner Coopetition in International Joint Ventures. Issue 3 (September 2017) - Shu, Chengli; Jin, Jason Lu; Zhou, Kevin Zheng
Is coopetition between foreign and local partners good or bad for international joint venture (IJV) performance? This study develops a contingent view to examine how the efficacy of coopetition is conditional on IJV characteristics (i.e., foreign equity share and partner cultural compatibility) and environmental factors (i.e., technological turbulence and market growth). The results from analyzing 194 IJVs in China reveal that coopetition fosters IJV performance under the conditions of high foreign equity share, low partner cultural compatibility, high technological turbulence, and/or high market growth. In contrast, coopetition hinders IJV performance at low levels of foreign equity share, technological turbulence, and/or market growth, or at high levels of partner cultural compatibility. These findings support the authors' contingent view of coopetition and provide novel insights for managing partner coopetition in IJVs.